Blends of agar/galactomannan for Marubakaido apple rootstock shoot proliferation - Lucyszyn,N. (2005)
Galactomannans (GMs) extracted from seeds of a native Brazilian specie designated Cassia fastuosa (cassia) and from Cyamopsis tetragonolobus (guar gum - a commercial GM) were mixed with agar, in the proportion of 3/3 g.L¹ (w/w), and used as a gelling agent in Marubakaido apple rootstock (Malus prunifolia Borkh) micropropagation. The rheological measurements of the gels showed a good interaction between both hidrocolloids. The micropropagation results on these media were compared with behaviour of standard medium containing agar only (6 g.L-1). Results from in vitro experiments indicated enhanced proliferation of apple shoots and also the occurrence of hyperhydric shoots was lower in the modified gel-medium.